Optimization of Infill Density, Layer Height, and Shell Thickness to Achieve Maximum Bending Strength and Minimum Printing Time of PLA 3D Printed Part - The Jaya Suteja; Rico Handoko; Arum Soesanti (Politeknik Negeri Lhokseumawe, 2023)
3D printing has advantages in making customized products, such as leg prosthetics. One of the required properties of 3D-printed leg prosthetics is their resistance to bending stress. Based on the literature review, the influence of the interaction among layer height, infill density, and shell thickness on the bending strength and printing time has not yet been investigated or optimized. This study aims to investigate the effect and optimize the layer height, infill density, and shell thickness to achieve the maximum bending strength and minimum printing time of a Polylactic Acid 3D printed part. This research studies three independent variables: layer height, infill density, and shell thickness. The independent variables of this research are bending strength and printing time. The bending test is conducted according to the ISO 178 standard. The printed specimen is tested using the bending testing machine Tarno Grocki to measure the maximum bending load the specimen can hold. The printing time is measured by using a stopwatch. The Response Surface Method is used as an optimization method to find the value of the maximum bending strength and minimum printing time of the 3D printed part. The optimum responses are achieved using 40 % infill density, 0.3 mm layer height, and 1.6 mm shell thickness. The maximum bending strength is 118. 5129 MPa and the minimum printing time is 11.1867 minutes.